Pengaruh Lime Saturation Faktor (LSF) Terhadap Kualitas C3S Dan Free Lime (FcaO) Pada Produksi Klinker PT. Semen Padang - Fithry , Dwi Annisa; Parmanaon, Durain; Rahmad, Alfein; Arbi, Raihan Alvaro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT Semen Padang is one of the largest cement companies in Indonesia, the process at PT Cement Padang consists of Raw Mill, Kiln, and Cement Mill units. One very important process is in the kiln where the process of burning raw mix materials into clinker occurs. Clinker is a product produced by burning a mixture of raw materials in the form of limestone, silica stone, clay, and iron sand which has become a Raw mix at high temperatures. The quality of clinker can affect the quality of cement, good quality will produce cement as desired, such as compressive strength, durability, and appropriate binding time. From this study, the incoming mass balance of 465.4501869 and the outgoing mass balance of 465.4364777 obtained a mass loss of 0.003%, while the incoming and outgoing energy balance is the same, namely 457,422,536.27.  By optimizing clinker production with the influence of lime saturation factor (LSF) on C3S and free lime (FcaO), the results obtained are in accordance with standardization.